The Role of Economic Policy Uncertainty in Renewable Energy-Growth Nexus: Evidence From the Rossi-Wang Causality Test - Lu, Zhou; Zhu, Linchuang; Lau, Chi Keung Marco; Isah, Aliyu Buhari; Zhu, Xiaoxian (Frontiers in Energy Research, 2021)
This paper examines the causal relationship between renewable energy consumption and economic growth in four countries: Brazil, Germany, Japan, and the United States. Unlike previous papers, we control economic policy uncertainty's effects to capture the role of capabilities on the renewable energy-growth nexus. The recent Vector Autoregression (VAR)-based Granger-causality test of Rossi-Wang shows a bidirectional causal relationship between renewable energy and the economic growth in Brazil and Germany. There is also a significant causality from renewables to economic growth in the United States.